National policy of Ukraine in culture in the evaluation intellectual elites and civil society experts (1999-2015) - Ivan Khoma (Cхід)
Euromaidan and dignity revolution, which further continues, clearly show that without change in the national policy of culture change the country will be very difficult. It's tactics and strategy formation space of life for the citizens of Ukraine, information about Ukrainian and country in the world, formed throughout history and established in today's harmful and humiliating stereotypes, myths. Obviously the official state culture has long been not satisfied an active, creative part of society. Outside the official data analysis of cultural policy meet in publications, cultural in content, authored by writers, critics, scholars and public figures.